Santiago de Chile Declaration - Naciones Suramericanas, Unión de (2016)
THE MINISTER AND MINISTERS OF DEFENSE, attending the First Meeting of the South American Defense Council (CDS) of the Union of South American Nations (UNASUR), in compliance with the mandate of the Heads of State and Government in the creation of the CDS and approval of its Statute on December 16, 2008 in Salvador, Brazil, meeting in the city of Santiago de Chile on March 9 and 10, 2009, reaffirm the unity of purposes that our countries reach today in the perspective of building a zone of peace and cooperation.